A Randomized Clinical Trial of Misoprostol and Oxytocin for Induction of Labour - Loto, OM; Ayuba, II; Adebara, IO; Ikuomola, AA; Onwudiegwu, U (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5061 NJOG 2010 Jul-Aug; 5(1): 44-48